Modern approaches to the treatment of retrosternal goiter - V. V. Grubnik; R. S. Parfentiev; V. M. Kosovan; N. D. Parfentieva (Клінічна хірургія)
Objective. To analyze the results of treatment of patients with retrosternal goiter.